The Existence of Grammatical Shifts in The English – Indonesian Translation Done by English Language Department Students - Bintang Shofiarizqi; Rahayu Puji Haryanti (Universitas Negeri Semarang, 2023)
Translation is transferring the meaning from the source language into the target language. Therefore, the shift in translation could be occurred because of the difference between two languages. To understand the translation shifts more detail, this study was composed by taking the translation shift as the theme of study. This study focused on explainning the existence of grammatical shifts in the English into Indonesian translation of an essay text done by the 5th semester students of English Language department at Walisongo Islamic State University. The subject of this study consisted of 15 people of 5th semester students of Universitas Islam Negeri Walisongo Semarang. Meanwhile, the object of this study was the translation results produced by the students. This study was a descriptive qualitative study emphasizing the detailed understanding of the result of the study. In order to collect the data, this study used test and documentation of the students’ translation results. Based on the analysis, there were found two main types of shifts, including level shift and category shift, in the students’ translation result. The category shift was divided into four types, such as structure shift, class shift, unit / rank shift, and intra-system shift. The dominant translation shift that found in this study was unit / rank shift as much as 28.81 %, that followed by structure shift (25.07 %), intra-system shift (20.89 %), level shift (18.53 %), and class shift (6.70 %). Those kinds of grammatical shifts will be explained in this study, in order to increase the knowledge about the grammatical shifts in translation.